Indonesian Migrant Workers in Malaysia and Their Social Environment: Analysis from a Socio-Legal Perspective - Bintang Parashtheo; Sri Wahyu Krida Sakti; Agus Suntoro; Tyas Retno Wulan (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
Malaysia is considered one of the primary destinations for migrants in Southeast Asia, particularly those from Indonesia. There are approximately 2.7 million Indonesian migrant workers in Malaysia, with 1.6 million having followed official placement procedures. The presence of a large number of Indonesian migrant workers in Malaysia has led to legal complications concerning their employment relationships with employers, including issues related to work contracts, safety regulations, social security, and termination of employment. Additionally, there are socio-legal concerns regarding the social integration of migrant workers into their new environment, which may contribute to criminal activities such as extremism, drug trafficking, human trafficking, undocumented labor, theft, and domestic violence. The legal problems faced by migrant workers are influenced by two main factors: their level of legal understanding, both in terms of Indonesian law and Malaysian law, and their lack of familiarity with the cultural norms of the host country, leading to social tensions. Therefore, the main question addressed in this study is how the social environment influences migrant workers' attitudes and behaviors, particularly whether it contributes to criminal acts and legal repercussions. This socio-legal study of the social relationship of Indonesian Migrant Workers with their environment is empirical using a survey method involving Indonesian Migrant Workers and document review. All data and legal materials are processed and analyzed using statistical instruments of central-tendency analysis for quantitative data, and interactive models of qualitative data analysis for qualitative data, while the analysis of the substance uses analytical theory of legal-protection and legal-justice.